2018
DOI: 10.1037/rep0000193
|View full text |Cite
|
Sign up to set email alerts
|

Treatment-seeking college students with disabilities: Presenting concerns, protective factors, and academic distress.

Abstract: These results suggest the importance of several factors in understanding the presenting concerns of treatment-seeking students with disabilities and mitigating academic distress for this population. Additional areas for research are presented. (PsycINFO Database Record

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 47 publications
(75 reference statements)
3
12
0
1
Order By: Relevance
“…Students with chronic illnesses face unique challenges, as they often move away from support networks [24], negotiate a new student identity [25] and face stigma and discrimination on university campuses [26]. O'Shea and Kaplan [27] found that students with psychiatric illnesses were engaged in a continuous process of meaning-making at an individual and social level to understand their disability.…”
Section: Students and Chronic Illnessesmentioning
confidence: 99%
“…Students with chronic illnesses face unique challenges, as they often move away from support networks [24], negotiate a new student identity [25] and face stigma and discrimination on university campuses [26]. O'Shea and Kaplan [27] found that students with psychiatric illnesses were engaged in a continuous process of meaning-making at an individual and social level to understand their disability.…”
Section: Students and Chronic Illnessesmentioning
confidence: 99%
“…Furthermore, counselors at UCCs should work with students to cultivate resources and supportive networks on campus, encouraging the establishment of collaborative networks with other campus-based health services and disability-related services. Leveraging these resources and networks is likely to benefit students with disabilities as they provide opportunities for shared experiences and social support, which have been found to negatively predict academic distress (Fleming et al, 2018). Moreover, the provision of services to students with disabilities should not be the sole responsibility of offices of disability support services.…”
Section: Implications For Practicementioning
confidence: 99%
“…Advisors should approach working with students with disabilities through the student engagement framework, placing the responsibility on advisors to connect these students to high-impact opportunities, instead of putting the onus on the students to seek out these opportunities themselves. Since stigma and disclosure are significant barriers for students with disabilities, advisors need additional professional development surrounding different aspects of disabilities and strategies to validate student concerns (Fleming et al, 2018). Faculty professional development that clearly identifies on-campus support available to students with disabilities, such as people, technology, and physical resources, will increase accessibility for these students.…”
Section: Implications For Practicementioning
confidence: 99%